MANVILLE: The ethics of economic efficiency? - Gini, A. R. (Journal of business ethics, 1984)
On Thursday, August 26, 1982 the Manville Corporation (formerly Johns-Manville) and its principle American and Canadian affiliates filed for reorganization under Chapter 11 in the United States District Court for the Southern District of New York. Manville's unexpected bankruptcy petition stunned the financial community, surprised Congress, shocked their creditors, suppliers and customers, totally outraged those who have filled damage suits against them and raised a complex tangle of legal, political and ethical issues that will have far reaching implications for millions of Americans. The drama of the Manville announcement stems from the fact that this is the same Manville Corporation which last year earned $60.3 million on sales exceeding $2 billion with an uncumbered net worth of $1.1 billion. This is the same Manville which ranks 181st on the ‘Fortune 500’ list of American corporations. And this is the same Manville which has been traditionally included in the 30 companies used to calculate the prestigious Dow Jones industrial average, the most watched indicator of prices on the New York Stock Exchange. While there are many factors in the equation that resulted in Manville's final decision, Manville Chairman John A. McKinney angerly announced that his company could no longer sustain or survive the blitz of ‘toxic torts’ that it was now facing., Many of Manville critics have claimed that Manville is acting in an immoral and illegal manner. They are held to be immoral insofar as their critics feel that they are using the ‘bankruptcy boom’ as a means of avoiding just compensation for those who have truly been injured or killed due to excessive or abusive exposure to asbestos. Manville is accused of acting illegally in that the spirit and purpose of the 1978 Bankruptcy Act is being violated because no company has ever filed for Chapter 11 given the size of their assets, their net worth and their yearly sales figures. Other observers suggest that this is much too simplistic a response to the situation and that whatever the final merits of Manville's petition the factors involved in their decision warrant a careful and detailed analysis.